Local Monophonic White Varieties Of Beans: Some Physical Properties And Especially The Amino Acid Composition - A. Bodoshov (MANAS: Journal of Engineering)
The aim of the work is to investigate some physical properties and amino acid composition of lopatka, kitayanka, saharniy beans varieties. Investigation of physical properties of beans is essential for design of equipment for harvesting, processing, transportation, cleaning, sorting, separation and packaging. In this research some physical properties of beans grains were studied such as shape, length, width and thickness of grains, mass of 1000 units and angle of repose. The hardness, bulk density were 0.43 mm, 0.08 mm, 0.05 mm and 685.11 kg/m3, 719.60 kg/m3, 666.84 kg/m3 respectively. In the second stage of work was studied total content of essential amino acids by high performance liquid chromatography. The investigation included sample preparation, derivatization and injection of the sample. The total content of essential amino acids in 100 g of saharniy, lopatka, kitayanka beans varieties 11.88 g, 9.03 g, 7.31 g respectively. Methionine was the amino acid limiting the quality of protein in the investigated samples. In addition the variety of the kitayanka beans the limiting amino acids were leucine, lysine, threonine and phenylalanine.Beans, monophonic bean varieties, protein, amino acid